Blue-to-green single photons from InGaN/GaN dot-in-a-nanowire ordered arrays. (July 2015) - Chernysheva, E.; Gačević, Ž.; García-Lepetit, N.; van der Meulen, H. P.; Müller, M.; Bertram, F.; Veit, P.; Torres-Pardo, A.; González Calbet, J. M.; Christen, J.; Calleja, E.; Calleja, J. M.; et al.
Abstract Single-photon emitters (SPEs) are at the basis of many applications for quantum information management. Semiconductor-based SPEs are best suited for practical implementations because of high design flexibility, scalability and integration potential in practical devices. Single-photon emission from ordered arrays of InGaN nano-disks embedded in GaN nanowires is reported. Intense and narrow optical emission lines from quantum dot-like recombination centers are observed in the blue-green spectral range. Characterization by electron microscopy, cathodoluminescence and micro-photoluminescence indicate that single photons are emitted from regions of high In concentration in the nano-disks due to alloy composition fluctuations. Single-photon emission is determined by photon correlation measurements showing deep anti-bunching minima in the second-order correlation function. The present results are a promising step towards the realization of on-site/on-demand single-photon sources in the blue-green spectral range operating in the GHz frequency range at high temperatures.